Morfologia, ultraestrutura e morfometria da glândula adrenal de paca (Cuniculus paca, Linnaeus, 1766) de cativeiro - Garcia Filho, Sergio Pinter [UNESP] (2014)
The agouti (Cuniculus paca, Linnaeus, 1766) is a medium size rodent although it belongs to Brazilian fauna, there is a little information in the literature about its morphology. Therefore, the aim of this study was to describe the morphological characteristics of their adrenal gland by analysis with light microscopy, scanning electron microscopy and transmission. This is important because adrenal gland is an organ that secrets particular substances in the body that promote biological functions and provides an anatomical basis in many areas of biomedical research for comparative studies. Ten adults agouti were used is this study, four males and four females, from Department Wild Animals of Faculdade de Ciências Agrárias e Veterinarias, UNESP- Jaboticabal, Jaboticabal-SP. After their euthanasia they were put in a supine position and their abdominal cavity was opened with an incision umbilical medline incision, followed by lateral abdominal wall removal to expose the gland.The adrenal glands were isolated, fragments were collected, fixed and prepared for histological and ultrastructural observation. The thickness of the layers adrenal cortex were measured and the results analyzed using descriptive statistics, Kruskal-Wallis test (p <0.01) and Dunn (p <0.05). It was found that the overall morphology of the adrenal gland paca resembles other mammals. Statistically layers of the adrenal cortex differ regarding their thicknesses